Effectiveness Analysis of Polder Drainage Systems in Reducing Urban Flood Risk: 1D/2D Hydrodynamic Simulation Based on LiDAR Topographic Data - Azizah Rokhmawati; Wati Asriningsih Pranoto; Heru Tri Saksena (Structures, Infrastructure, Planning, Implementation, and Legislation, 2026)
Rapid urbanization in coastal regions experiencing severe land subsidence has significantly heightened urban flood vulnerability, necessitating high-precision polder drainage systems. This research aims to evaluate the effectiveness of polder mechanisms in mitigating flood risks while simultaneously assessing the geotechnical integrity of channel embankments during operational phases. Utilizing a quantitative design based on 1D/2D hydrodynamic simulations, this study leverages high-resolution 0.5-meter LiDAR topographic data from the Geospatial Information Agency (BIG), covering a 1,250-hectare catchment area in West Semarang. Official secondary data from the Ministry of Public Works and Housing (PUPR) regarding pump specifications and geotechnical parameters including cohesion and internal friction angles were integrated to simulate 10 to 50-year rainfall return periods and rapid drawdown conditions. The results demonstrate that the polder system curtails the average inundation extent by 73.51%, with high model reliability (). However, geotechnical analysis reveals that excessive water evacuation rates (0.85 m/hour) diminish the Factor of Safety (FS) to a critical level of 1.08, falling below the safety threshold of 1.25. These implications suggest that pump operational policies must be synchronized with soil stability limits to forestall structural failures. This study concludes that the integration of LiDAR data and geotechnical parameters is vital for the sustainability of polder infrastructure. Future research is encouraged to explore automated pumping systems controlled by pore water pressure sensors to optimize both safety and efficiency in urban drainage management.